Evolution of textures and microstructures in IF-steel sheets during continuous confined strip shearing and subsequent recrystallization annealing - Jin, YH; Huh, MY; Chung, YH (SPRINGER, 2004)
Interstitial free (IF) steel sheets were deformed by continuous confined strip shearing (CCSS) based on the equal channel angular pressing (ECAP). The samples were deformed by CCSS up to three passages and subsequently recrystallized at 700degreesC for 1 h. The strain history of IF steel sheets in the CCSS die-channel was tackled by finite element method (FEM) simulations. The deformation by CCSS led to the shear deformation and consequently the formation of shear texture components. With increasing number of CCSS passages, the intensity of the deformation texture was hardly increased. The recrystallization texture resembled the deformation texture. The orientation stability was discussed by mean of Taylor deformation model and the formation of recrystallization textures was discussed by occurrence of the discontinuous recrystallization. Observations by transmission electron microscopy (TEM) and electron backscattered diffraction (EBSD) revealed the formation of ultra-fine grains in IF sheets deformed by CCSS. (C) 2004 Kluwer Academic Publishers.
Keywords: DEFORMATION; STRAIN